How Can Clinical Teams Support Patients With a Brain Tumour Diagnosis With Sex Relationships and Intimacy?. (1st October 2022) - Kostick, Ellie; La, Jessica; Hurwitz, Victoria; Hedges, Sarah; Robinson, Charlotte; Suarez, Aeron; Ashkan, Keyoumars; Bhangoo, Ranjeev; Gullan, Richard; Vergani, Francesco; Brazil, Lucy; Al-Salihi, Omar; et al.
Abstract: AIMS: There is a gap in supporting patients with sexual relationships and intimacy. The aim of this study is to establish if patients with a brain tumour feel they are able to ask questions and concerns about sex, relationships and intimacy following diagnosis; is there an unmet need and how can this be addressed. METHOD: An anonymous survey was sent to patients known to a neuro-oncology team. Questions were in relation to their experiences of sex relationships and intimacy. Patients were asked if they had concerns about changes in their relationships since their diagnosis. They were also asked for their comments on the subject so we can better understand how as a service we can improve to ensure holistic care. RESULTS: There are 40 responses. The majority of respondents had concerns about their relationship since diagnosis and that their relationships have changed. 57% were concerned about a physical relationship with a partner/ future partners. 50% agreed their physical relationship had changed. 45% of people agreeing their emotional relationships have changed. 38 out of the 40 people questioned, had not asked their clinical team for advice about sex and relationships. 46% suggested clinicians initiating these conversations. CONCLUSION: Sex relationships and intimacy are significant for most adult populations, encompassing connection with their loved ones, self esteem and psychological and emotional well-being. With brain tumour diagnosis this part of people's lives can hugely impacted. Historically clinicians have found this a difficult subject to discuss. Further work is required to understand the barriers initiating this subject